Acquisition of German pluralization rules in monolingual and multilingual children - Zaretsky, Eugen; Lange, Benjamin P.; Euler, Harald A.; Neumann, Katrin (Studies in Second Language Learning and Teaching, 2013)
Existing studies on plural acquisition in German have relied on small samples and thus hardly deliver generalizable and differentiated results. Here, overgeneralizations of certain plural allomorphs and other tendencies in the acquisition of German plural markers are described on the basis of test data from 7,394 3- to 5-yearold monolingual German and bi/multilingual immigrant children tested with a modified, validated version of the Marburger Sprachscreening (MSS) language test and 476 children tested with the SETK 3-5 language test. Classified correct and wrong answers to MSS and SETK 3-5 plural items were compared. The acquisition patterns of immigrants corresponded to those of younger German children. Both monolingual German and immigrant children demonstrated generally the same universal frequency and phonetically/phonologically based error patterns, irrespective of their linguistic background, but with different tendencies such as overgeneralization of -s by German children only.